Transparansi dan Akuntabilitas dalam Pengelolaan Dana Bos: Mengidentifikasi Penyebab Penyelewengan - Umdatul Mursiyah; Siti Apipah Zachroh; Aprilliantoni (CV. Creative Tugu Pena, 2024)
This study attempts to analyze the factors underlying the misappropriation or abuse of BOS funds in the school environment and to formulate strategic steps that can be taken to prevent such misappropriation. Thus, the management of BOS funds can be carried out transparently and accountably. This study uses a literature review method with library research data collection techniques. Data were collected from various journals, articles, and official documents related to BOS fund management, transparency, and accountability. The analysis was conducted to identify patterns of misappropriation of funds and good fund management methods. The results of this study indicate that there are several underlying factors causing the misappropriation of BOS funds, including: Lack of supervision and transparency, lack of understanding of the regulations on the use of funds, and a deep-rooted culture of corruption. The conclusion of this study is that in order to increase transparency and accountability in the management of BOS funds, it is necessary to improve the capabilities of human resources (HR) through training on regulations and the use of information technology. It is hoped that this recommendation will help the government and related parties in creating a better BOS fund management system because community participation must be increased so that they can play an active role in supervising the use of BOS funds